Design of a GSM Based Switching and Monitoring System Using a Mobile Phone. - Bbaale Francis (Kabale University, 2023)
With the increase in energy consumption due high population, there is a great need to conserve energy in all ways. The inability to access and control the appliances from remote locations is one of the major reasons for energy wastage in Uganda. This project presents the development and implementation of a Global System for Mobile Communication (GSM) based switching and monitoring system for electrical appliances and lighting that enables complete control of the interface on which it is based. GSM Shield was used for receiving short message service (SMS) from the appliance owner’s mobile phone that automatically enables an Arduino microcontroller to take the necessary actions like switching OFF and ON electrical appliances such as fan, light, air- conditioner, and so on. Basically, it reads the SMS and acts according to the message. Similar products commercially available are Internet dependent and so lack the true sense of real mobility and security. However, the present GSM based remote control system allows the electrical appliance owner to switch or monitor electrical appliances from anywhere using the mobile phone and also prevents unauthorized access to these appliances. This GSM based switching and monitoring system is recommended for implementation in homes, offices and industries to prevent appliance damage due over heating, for security purposes and to tackle the rampant energy wastage in Uganda